Investigation on the anti-aging properties enhancement mechanism of graphene on RA based on size effect. (December 2022) - Liao, Meijie; Gao, Yingli; Xie, Yutong; Zhu, Juncai; Li, Zhengkang; Tian, Weiwei; Zhu, Zhanghuang
Abstract: The application of rubber powder to modify asphalt has become one of the main ways of resourceful and harmless utilization of waste tire rubber. However, rubber powder is prone to degradation during service, and this deficiency limits its further development. To solve the problem of insufficient aging resistance of RA, multi-layer graphene with different sizes was adopted to modify it. The aging resistance of modified asphalt was evaluated by high-temperature dynamic shear test(DSR), low-temperature bending beam test (BBR), and Brookfield rotational viscosity test (RV), and the microscopic mechanism was investigated by Fourier infrared spectroscopy (FTIR) and Four-component analysis(SARA). Furthermore, the aging model of modified asphalt was established by combining the content of asphalt components and the number of oxidation functional groups using MD technology, to reveal the size effect and anti-aging mechanism of graphene from a molecular perspective. In the molecular simulation section, the radial distribution function (RDF), mean square displacement (MSD), glass transition temperature (TG), and viscosity of the model were compared and analyzed. Macroscopic tests showed that graphene could improve the rheological properties and viscosity of RA, and the graphene with a smaller size has a more obvious improvement of asphalt anti-aging properties. Comparing the carbonyl index and carboxyl index of the four components before and after asphalt aging, it can be found that, graphene mainly relies on the inhibition of the oxidation of saturated phenols to improve the aging resistance of asphalt. In further simulation analysis, the glass transition behavior and viscosity simulation of the asphalt model confirmed the above conclusion and further revealed that the modification mechanism of graphene is related to its size. The high surface of small-sized graphene adsorbs more light components and forms a "micelle core", which inhibits the tendency of resin, aromatic, and asphaltene rearrangement during aging. In addition, graphene increases the energy within asphalt molecules and decreases the energy between asphalt molecules, which leads to more active intermolecular motion and promotes uniform dispersion of asphalt micelles in the dispersion medium. This research can offer a theoretical guideline for optimizing the use of graphene in modified asphalt.